REM sleep is associated with distinct global cortical dynamics and controlled by occipital cortex - Wang, Ziyue; Fei, Xiang; Liu, Xiaotong; Wang, Yanjie; Hu, Yue; Peng, Wanling; Wang, Ying-wei; Zhang, Siyu; Xu, Min (Nature communications, 2022)
The cerebral cortex is spontaneously active during sleep, yet it is unclear how this global cortical activity is spatiotemporally organized, and whether such activity not only reflects sleep states but also contributes to sleep state switching. Here we report that cortex-wide calcium imaging in mice revealed distinct sleep stage-dependent spatiotemporal patterns of global cortical activity, and modulation of such patterns could regulate sleep state switching. In particular, elevated activation in the occipital cortical regions (including the retrosplenial cortex and visual areas) became dominant during rapid-eye-movement (REM) sleep. Furthermore, such pontogeniculooccipital (PGO) wave-like activity was associated with transitions to REM sleep, and optogenetic inhibition of occipital activity strongly promoted deep sleep by suppressing the NREM-to-REM transition. Thus, whereas subcortical networks are critical for initiating and maintaining sleep and wakefulness states, distinct global cortical activity also plays an active role in controlling sleep states. The cortex is very active during sleep. Wang et al. used macroscopic Ca 2+ imaging to record the global cortical activity from the entire dorsal cortex of mice during sleep and uncover an unexpected role of the cortex in controlling REM sleep.